Detecting defect requirements in animation-based reading learning using perspective-based reading - Haryamadha, Rama; Saputra, Roy Inzaqhi; Aminudin, Aminudin; Nuryasin, Ilyas (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Defects in the requirements specification can have severe consequences throughout the software development life cycle. Some of these can result in poor product quality due to incorrect or missing quality characteristics, such as the design of the user interface. The goal of this study is to detecting defect requirements in animation-based reading learning using perspective-based reading. But often the design is not in line with the specifications of the requirements of users and developers when developing this application. Therefore we use a user persona approach to find out what needs are needed in animation learning and Perspective Based Reading (PBR) for verification or validation effective from the development of this learning application user interface, from the results of this study a total of 1 defect was obtained for the UI development of animation-based reading learning, and from the user's perspective there were no defects, and it is hoped that from this research to improve develop learning applications that are more interactive and in accordance with the requirements of stakeholders.